MANAJEMEN PERPUSTAKAAN MODERN DALAM PROSES PEMBELAJARAN - Fahmi, Agus (Universitas Pendidikan Mandalika, 2022)
Abstract: The learning process is the tendency of a person's heart in an individual's efforts to obtain a new behavior change. The purpose of this study was to find out: